(untitled) (Journal of The Colloquium for Information Systems Security Education, 2016)
In order to improve the abilities of students to write robust programs (“secure programming”) without adding new classes or material in existing classes, a Secure Programming Clinic that functions analogously to an English writing clinic has been developed. This paper reports on preliminary results from an instance of the clinic at a large university. Given the statistics obtained from this trial, the clinic improved the students’ secure programming behavior and helped students develop a deeper understanding of secure programming concepts.